PERANCANGAN MAINTENANCE MESIN HOIST TULANGAN DENGAN MENGGUNAKAN METODE LEAN MAINTENACE (STUDI KASUS: PT. XYZ) - Winan Azhari, (2020)
PT. XYZ is a company engaged in manufacturing concrete. There are many machines that used in this company, one of them is the Reinforcement Hoist machine. The Reinforcement Hoist machine is the engine with the highest downtime on line 8 during 2019 with 90 hours.The maintenance system that applied in this company is corrective maintenance. To implement a preventive maintenance system, researcher has used the Lean Maintenance method to find the MTTF value for each component and analyzing maintenance activities by Maintenance Value Stream Mapping (MVSM).The purpose of this research was to determine the critical components of the Reinforcement Hoist machine using FMEA, determine the reliability value of machine using RBD, determine preventive scheduling using selected distributions, and calculate maintenance efficiency using the Lean Maintenance method. From the results of the FMEA critical components are the Gearbox and End Carriage components. The Reliability Value of the Reinforcement Hoist engine is 85.69% with MTTF Gearbox component every 3 days and the End Carriage component every 6 days. The results of the Maintenance Efficiency of the Gearbox component are 49.59% and the End Carriage component is 61.35%